Metformin And Vitamin B12 Status In Patients: A Systematic Review (Journal of Pharmaceutical Negative Results, 2022)
Metformin's effects on vitamin B12 decrease have been the subject of mixed findings from randomised controlled trials and observational research. Therefore, we conducted a comprehensive review to investigate whether or not metformin affects serum levels of vitamin B12.